On phase trajectory of dynamic system "directionally crystallized binary melt" - Kanishchev, V.M.; Semynozhenko, V.P. (Functional Materials, 2014)
The origin of return and self-crossing points on the parametrically specified curves of crystallization rate vs. impurities concentration at the interface during pulling a crystal from a binary melt at constant rate in the initial transitional stage has been explained.